Parametric study of bolted and adhesive connections and experimental creep tests in adhesive connections under high temperature and long term loading - Gomes, Miguel Miranda Pedro (2014)
Dissertação de Mestrado Integrado em Engenharia Civil apresentada à Faculdade de Ciências e Tecnologia da Universidade de Coimbra